Phenotypic plasticity during early ontogeny in cultured turbot (Scophthalmus maximus): changes in dorsal and anal fin ray counts by water temperature. (August 2014) - Torres‐Núñez, E.; Cal, R.; Rotllant, J.
Summary Plastic responses to environmental conditions are crucial among ectothermic organisms, and any traits induced early in ontogeny may have long‐term effects. Here, we studied how turbot larvae altered their morphology in three different thermal environments and assessed whether different thermal regimes affected the survival, growth, development and morphology of juvenile turbot at the end of metamorphosis. Therefore, newly hatched Turbot (Scopthalmus maximux L.) larvae were divided into three groups and reared at 14, 18 and 22°C until 80 days after hatching. Environmental temperature was seen to affect several turbot traits. Low temperature induced low dorsal and anal fin ray counts, but had no effect on gross body morphology. There were differences in growth and skeletal development rates, but no differences in survival. There were also no differences in the skeletal malformations occurring in response to environmental temperature treatment. Collectively, these results supported the idea of the existence of a thermal plastic response, as found, in other fish species.